Field-induced nematic-like magnetic transition in an iron pnictide superconductor, Ca$_{10}$(Pt$_{3}$As$_{8}$)((Fe$_{1-x}$Pt$_{x}$)$_{2}$As$_{2}$)$_{5}$ - Watson, MD; McCollam, A; Blake, S; Vignolles, D; Drigo, L; Mazin, I; Guterding, D; Jeschke, H; Valenti, R; Ni, N; Cava, R; Coldea, A (American Physical Society, 2013)
We report a high magnetic field study up to 55 T of the nearly optimally doped iron-pnictide superconductor Ca$_{10}$(Pt$_{3}$As$_{8}$) ((Fe$_{1-x}$Pt$_{x}$)$_{2}$As$_{2}$)$_{5}$ (x=0.078(6)) with a Tc 10 K using magnetic torque, tunnel diode oscillator technique and transport measurements. We determine the superconducting phase diagram, revealing an anisotropy of the irreversibility field up to a factor of 10 near Tc and signatures of multiband superconductivity. Unexpectedly, we find a spin-flop like anomaly in magnetic torque at 22 T, when the magnetic field is applied perpendicular to the ab planes, which becomes significantly more pronounced as the temperature is lowered to 0.33 K. As our superconducting sample lies well outside the antiferromagnetic region of the phase diagram, the observed field-induced transition in torque indicates a spin-flop transition not of long-range ordered moments, but of nematic-like antiferromagnetic fluctuations.